The Effect of Cervical Canal Cleaning Before IUI in Infertile Couples - Katayoon Berjis; Ozra Azmodeh; Firouzeh Asbagh; Nasser Salsabili; Mansoureh Moaya; Golsa Jodi (Tehran University of Medical Sciences, 2010)
Objective: Intrauterine insemination (IUI) is known as a routine method for infertility treatment. The effectiveness of IUI is not identical in all cases. So in this study to evaluate different methods of IUI in order to increase pregnancy rate, IUI with cleaning cervical canal by swab is compared to IUI without cervical canal cleaning. Material and methods: This study was conducted from 2008/2/1 to 2008/9/30 in MirzaKochak Khan Infertility center. Totally 224 cases were selected for IUI divided into two groups. Group one (n=112) had cervical cleaning with swab before IUI and group two (n=112) was control group. Pregnancy rate were compared in two groups. Results: Two groups were matched regarding age, type of infertility and number of follicles. Pregnancy rate in cervical canal cleaning (group one) and control group (group two) was 15.1% and 9.8% respectively. The difference was not significant. Conclusion: In this study with cleaning cervical canal by swab before IUI there was a non-significant increase in pregnancy rate.